Organic amendments boost soil fertility and rice productivity and reduce methane emissions from paddy fields under sub-tropical conditions - Haque, Md Mahamudul; Datta, Juel; Ahmed, Tareq; Ehsanullah, Md; Karim, Md Neaul; Akter, Mt. Samima; Iqbal, Muhammad Aamir; Baazeem, Alaa; Hadifa, Adel; Ahmed, Sharif; EL Sabagh, Ayman (MDPI, 2021)
Deteriorating soil fertility and gradually decreasing rice productivity along with higher greenhouse gas emissions from paddy fields have emerged as serious threats to the sustainability of rice production and food security. Rice production in the subtropical environment in Bangladesh is mostly dependent on synthetic inorganic fertilizer to maintain productivity; however, the inorganic fertilizer has negative effects on global warming. Climate-smart and resilient agricultural production systems are major concerns nowadays to meet sustainable development goals. The study was conducted to evaluate the optimum rate and source of organic amendments on rice productivity and soil fertility along with CH4 emission. A total of nine nutrient combinations were used in the study. The CH4 emission, soil redox potential (Eh), soil pH, soil nitrogen and organic carbon, available phosphorus, rice grain and straw were greatly affected by the application of different rates and sources of the nutrient. However, the soil exchangeable K content, plant height, and harvest index were not affected. Among the treatments, the application of 75% recommended fertilizer (RF) + biosolid 2 t ha−1 (T3) was the most effective and showed the superior performance in terms of available P (12.90 ppm), the number of grains panicle−1 (121), and 1000-grain weight (24.6g), rice grain, and straw yield along with the moderate CH4 emission (18.25 mg m−2h−1). On the other hand, the lowest soil Eh (−158 mV) and soil pH (6.65) were measured from the treatment T3. The finding of this study revealed that the application of 75% of RF + biosolid 2 t ha−1 can be recommended as the preferable soil amendment for boosting rice yield, reduce CH4 emissions, and sustainably maintain soil fertility. Furthermore, this finding may help to introduce preferable soil amendment doses, which will contribute to boosting rice productivity and economic turnouts of the farmers.